The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the Proceedings of the Third Workshop on Multidisciplinary and Its Applications, WMA-3 2019, 11-14 December 2019 2020
DOI: 10.4108/eai.11-12-2019.2290817
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Preference Selection Index Method In Determination of People’s Business Credit Receiver

Abstract: Decision support system is an information system that helps decision makers in solving unstructured problems. Implementation of method methods in problem solving will make the results provided by decision support systems more effective and accurate. In this study researchers discussed the implementation of Preference Selection Index in producing business actors who will get the People's Business Credit fund. The application of the PSI method in this case helps decision makers without having to give weight to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…PSI method is a method that meets this requirement [19]. Based on this advantage, the PSI method has been applied to rank the alternatives and then choose the best one in many different fields: measuring the performances of the machines [20], ranking of waste recovery alternatives [21]; developing a student scholarship decision support system [22], optimization selection of ceramic particulate reinforced dental restorative composite materials [23]; decision making over the design stage of production system life cycle [24]; optimization of turning process parameters [25]; determining the location of used laptop marketing [26]; comparison of tourism potentinals [27]; machine selection in a flexible manufacturing cell [28]; to select personnel for a textile company in Turkey, to select an industrial robot, to select a turning process, and to evaluate the air quality in the office [29]; to select individuals eligible for credit loans from banks [30]; to select the outer circular grinding process [31]; etc. However, despite taking a lot of time and effort, the author of this research has not found any studies that applied PSI method in 3D printer selection.…”
Section: Introductionmentioning
confidence: 99%
“…PSI method is a method that meets this requirement [19]. Based on this advantage, the PSI method has been applied to rank the alternatives and then choose the best one in many different fields: measuring the performances of the machines [20], ranking of waste recovery alternatives [21]; developing a student scholarship decision support system [22], optimization selection of ceramic particulate reinforced dental restorative composite materials [23]; decision making over the design stage of production system life cycle [24]; optimization of turning process parameters [25]; determining the location of used laptop marketing [26]; comparison of tourism potentinals [27]; machine selection in a flexible manufacturing cell [28]; to select personnel for a textile company in Turkey, to select an industrial robot, to select a turning process, and to evaluate the air quality in the office [29]; to select individuals eligible for credit loans from banks [30]; to select the outer circular grinding process [31]; etc. However, despite taking a lot of time and effort, the author of this research has not found any studies that applied PSI method in 3D printer selection.…”
Section: Introductionmentioning
confidence: 99%